Development Of Fintech in Islamic Social Finance in Malaysia - Muhammad Iqmal Hisham Kamaruddin; Mustafa Mohd Hanefah; Amir Shaharuddin; Abdullah Mohammed Ahmed Ayedh; Nur Adilah Othman (International Islamic University Malaysia, 2024)
Indexed by WOS